2020
DOI: 10.1177/2192568220964032
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use Is Associated With Increased 90-Day Readmission Among Patients Undergoing Surgery for Degenerative Spine Disease

Abstract: Study Design: Retrospective database study. Objective: Tobacco use is associated with complications after surgical procedures, including poor wound healing, surgical site infections, and cardiovascular events. We used the Nationwide Readmissions Database (NRD) to determine if tobacco use is associated with increased 30- and 90-day readmission among patients undergoing surgery for degenerative spine disorders. Methods: Patients who underwent elective spine surgery were identified in the NRD from 2010 to 2014. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Smoking history is known to be associated with postoperative complications, such as surgical site infection, which can affect the incidence of readmission secondarily. 18 19 Patients are also recommended to stop smoking as it can have adverse effects on wound healing and surgical site infections. In our study, current smoking was not significantly associated with the incidence of unplanned readmission after ACDF (OR, 1.07; 95% CI, 0.94–1.23; p =0.3).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking history is known to be associated with postoperative complications, such as surgical site infection, which can affect the incidence of readmission secondarily. 18 19 Patients are also recommended to stop smoking as it can have adverse effects on wound healing and surgical site infections. In our study, current smoking was not significantly associated with the incidence of unplanned readmission after ACDF (OR, 1.07; 95% CI, 0.94–1.23; p =0.3).…”
Section: Discussionmentioning
confidence: 99%
“…39 40 41 42 Current smoking is associated with higher rates of intensive care admission, hospital stay, and readmission. 38 41 43 44 Finally, multiple studies have shown an association between current smoking and postoperative mortality. 44 45 46 One large study using American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) data propensity matched over 80,000 current and nonsmokers.…”
Section: Risks Of Smoking In the Perioperative Periodmentioning
confidence: 99%
“…38 41 43 44 Finally, multiple studies have shown an association between current smoking and postoperative mortality. 44 45 46 One large study using American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) data propensity matched over 80,000 current and nonsmokers. Patients who currently smoked had a 1.38 times increased odds of 30-day mortality compared with nonsmokers (95% CI: 1.11–1.72).…”
Section: Risks Of Smoking In the Perioperative Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster 3 was associated with risk factors and prevention of IASIS. The main concerns of IASIS in cluster 3 appeared to focus on obesity, body mass index, urinary tract infection, diabetes, albumin, malnutrition, smoking, and rheumatoid arthritis (54)(55)(56)(57)(58)(59)(60)(61). Vancomycin powder is the most relevant research topic in IASIS prevention, and the efficacy of local vancomycin powder in decreasing the infection rate after spine surgery has become a research hotspot involving considerable controversy (62,63).…”
Section: Research Direction and Trendsmentioning
confidence: 99%